Minimum wages and wage compression in Belgian industries - Sem Vandekerckhove; Sam Desiere; Karolien Lenaerts (National Bank of Belgium, 2020)
Measuring the effects minimum wages have on wage inequality and employment is complex, and troubled by endogeneity issues. We use a large longitudinal dataset and sectoral minimum wage variation to analyse trends in minimum wages and wage inequality in Belgium. Building on the model of Lee (1999) and the critique by Autor, Manning and Smith (2014), we find that minimum wage increases in Belgium cause a two-sided compression of the wage distribution. Using wage indexation as a natural instrument, we find an additional source of endogeneity in sectoral bargaining. It appears that unions and employer's representatives prefer increasing lower wages over higher wages. This paper explores several hypotheses that could explain this outcome, including firm proximity to sectoral wage bargaining, and labour supply elasticity. The results suggest that a higher likelihood of firm involvement in the bargaining process indeed enhances "endogenous" wage setting, in which minimum wage levels and wage dispersion are simultaneously determined. A similar finding appears in absence of white-collar workers, pointing to different degrees of internal redistribution in sectors depending on the outside options of workers. The minimum wage effects found when including sectoral characteristics can contribute to understanding different minimum wage effects encountered in other and future research, and advise policy makers to consider the criteria to judiciously set minimum wages at the right level through collective bargaining.
Keywords: J31; J52; 330; Minimum wages; Wage inequality; Collective bargaining; Wage compression